Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1111/resp.14487
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer screening an asbestos exposed population: Existing lung cancer risk criteria are not sufficient

Abstract: Background and Objective Asbestos is a major risk factor for lung cancer, with or without tobacco smoke exposure. Low dose computed tomography (LDCT) screening for early lung cancer is effective but only when targeting high risk populations. This study aimed to analyse the effectiveness of LDCT screening in an asbestos exposed population and to compare lung cancer screening program (LCSP) eligibility criteria. Methods Participants in an asbestos health surveillance program, the Western Australia Asbestos Revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Nine nonrandomized studies of asbestos-exposed populations with ≥150 participants reported results of LDCT screening for lung cancer between 2002 and 2019. [65][66][67][68][69][70][71][72][73][74] Age, smoking history, and asbestos exposure were principal or exclusive eligibility criteria with frequent use of broader age and smoking ranges than those used in NLST or NELSON. These studies were included in a published systematic review and meta-analyses by Ollier et al 75 and Maisonneuve et al 73 None of these studies used risk prediction models, NLST, or NELSON eligibility criteria to determine eligibility.…”
Section: Asbestosmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine nonrandomized studies of asbestos-exposed populations with ≥150 participants reported results of LDCT screening for lung cancer between 2002 and 2019. [65][66][67][68][69][70][71][72][73][74] Age, smoking history, and asbestos exposure were principal or exclusive eligibility criteria with frequent use of broader age and smoking ranges than those used in NLST or NELSON. These studies were included in a published systematic review and meta-analyses by Ollier et al 75 and Maisonneuve et al 73 None of these studies used risk prediction models, NLST, or NELSON eligibility criteria to determine eligibility.…”
Section: Asbestosmentioning
confidence: 99%
“…Brims and colleagues conclude that existing lung cancer screening criteria do not adequately account for occupational exposures. 74…”
Section: Asbestosmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent publication in Respirology by Brims et al 11 shows again that screening criteria based on age and pack‐years fail to optimally capture individuals at risk. Data from 1743 participants in the Western Australia Asbestos Review Program were collected including a description of occupation and residency.…”
mentioning
confidence: 99%